The Integration of Sufism and Sharia in Buya Hamka's Thought and Its Relevance to Children's Character Education - Abdul Basit Atamimi; Athoillah Islamy; M Rifky Aziiz Yusuf; Sofyan Sururi (CV. Creative Tugu Pena, 2026)
This study aims to describe the dimensions of integration Sufism and sharia in Buya Hamka's thinking and its relevance in children's character education. The focus of the study is on the relevance of the values of Sufism and Sharia integration, which emphasize a balance between ritual piety and social involvement as instruments for strengthening mental resilience and spiritual intelligence in children. The research method used is qualitative with a literature study approach and content analysis of the main text in Buya Hamka's book Tasawuf Modern (Modern Sufism). The results of the study show that Hamka's interpretation of the concepts of zuhud and qana'ah does not mean avoiding the world, but rather self-control over the flow of information and materialism. This Sufi interpretation can produce a paradigm model of Islamic religiosity that harmonizes morality and formalistic legal aspects, which can become the basis for strengthening character education for children in facing the pressures of modernity. This study contributes to the importance of integrating Sufism and Sharia as ethical and psychological foundations in children's character education.